Self-care for maternal and reproductive health in conflict settings: qualitative case study in Nuba Mountains, Sudan - Sali Hafez; Sali Hafez; Stella Sadia Samson; Lydia Tanner; Naomi Pendle; Naomi Pendle (Frontiers Media S.A., 2024)
IntroductionSelf-care is a critical component of Reproductive, Maternal, and Neonatal Health (RMNH), offering women the knowledge, skills, and autonomy needed for well-being throughout the reproductive cycle. This paper explores the significance of self-care in conflict-affected regions, where access to formal healthcare is limited. Such areas place pregnant women at higher risk due to increased incidents of adverse events during pregnancy and childbirth. Self-care interventions have the potential to enhance access to quality healthcare services.MethodsEmploying a qualitative approach, this study explores RMNH self-care practices among pregnant and post-natal women in the Nuba Mountains. The methods included in-depth semi-structured interviews with 24 participants, comprising pregnant women, recent mothers, and healthcare providers. Purposive sampling was used to capture the experiences of mothers, and thematic analysis identified key patterns and themes in self-care practices. The perspectives of healthcare professionals were included to understand the context of RMNH care in conflict settings.ResultsThe study revealed the crucial role of community cohesion in providing emotional and practical support in pregnancy, childbirth, and in the post-natal period. Limited healthcare infrastructure and ongoing conflict-related challenges provided important drivers for self-care practices. A spectrum of self-care interventions ranged from personal hygiene practices to community-supported childbirth and postnatal care. Significant reliance on elder women's wisdom and traditional midwifery was observed, particularly in the absence of formal healthcare facilities. Some women moved to live with family close to the hospital in the weeks before their due dates in order to mitigate the risks of early deliveries, complications, or general insecurity in their home areas.DiscussionThe findings present a compelling narrative of communal self-care, challenging the conventional notion of self-care as solely individualistic. In this setting, the community's role is fundamental, with knowledge sharing and mutual support forming the bedrock of maternal health practices. Elder women, embodying repositories of perceived traditional wisdom, emerge as central figures, guiding pregnant and postpartum women through shared experiences and practices. This collective approach is not merely a cultural characteristic but a necessity born out of the region's limited healthcare infrastructure and ongoing conflict. The study underscores the need to recognize and integrate these communal self-care strategies into broader health interventions.